2016
DOI: 10.22599/bioj.101
|View full text |Cite
|
Sign up to set email alerts
|

How do undergraduate medical students learn ophthalmology in a clinical environment?

Abstract: Aim: This phenomenological study looked at the nature of undergraduate medical student learning in an ophthalmology environment. The study set out to identify what influences the quality of medical students' educational experience in ophthalmology. The study was conducted on 17 final-year medical students from a medical school in the west of Ireland, after undertaking their 3-week combined clinicalbased ophthalmology/neurology programme at a tertiary referral teaching hospital. Methods: Learning diaries were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…The students were also performed basic ophthalmology examinations under the supervision of the instructor. As an adjunct to conventional learning method, however, online learning may be beneficial and may have a significant impact on future medical students, including new opportunities in patient care and technical skill development [1,[18][19][20][21]. This study's limitations include the relatively small sample size and the self-reported nature of the questionnaire in which participants may be subject to reporting bias affected by student confidence and the degree to which they did not want to disappoint teaching staff.…”
Section: Resultsmentioning
confidence: 99%
“…The students were also performed basic ophthalmology examinations under the supervision of the instructor. As an adjunct to conventional learning method, however, online learning may be beneficial and may have a significant impact on future medical students, including new opportunities in patient care and technical skill development [1,[18][19][20][21]. This study's limitations include the relatively small sample size and the self-reported nature of the questionnaire in which participants may be subject to reporting bias affected by student confidence and the degree to which they did not want to disappoint teaching staff.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, é importante enfatizar o que foi analisado no artigo "How do undergraduate medical students learn ophthalmology in a clinical environment?" (5). Esse estudo analisou alunos do último ano de uma escola de Medicina no Oeste da Irlanda, com o intuito de identificar o que influencia a qualidade da experiência educacional dos estudantes de Medicina em Oftalmologia.…”
Section: Gráficounclassified